Use of prebiotics in oral delivery of bioactive compounds: a nanotechnology perspective - F., Heidarpour; M.R, Mohammadabadi; Sarker, Md. Zaidul Islam; B., Maherani; N., Saari; A.A, Hamid; F., Abas; M.Y.A, Manap; M.R, Mozafari (Govi Verlag Pharmazeutischer Verlag GmbH, 2011)
The oral route is considered the most patient-convenient means of drug administration. In recent years there has been a tendency to employ smart carrier systems that enable controlled or timed release of a bioactive material, thereby providing a better dosing pattern and minimizing side effects. Nano-encapsulation systems (nanocarriers) offer important advantages over conventional drug delivery techniques. Nanocarriers can protect the drug from chemical/enzymatic degradation and enhance bioavailability. Prebiotics are ideal ingredients for the nano-encapsulation and oral drug delivery due to their natural ability to protect the encapsulated compound in the upper gasterointestinal (GI) tract. Here the potential of prebiotics for oral delivery of drugs and other bioactives is reviewed.